Oral Mucosal Complications and Oral Hygiene Practice Among Diabetic and Non-Diabetic Patients - Ayesha Bibi, Maheen Aqeeq, Atiqa Ashraf, Faiha Tanveer, Rida Khaliq, Tahoora Ahmad, (Pakistan Journal of Medical & Health Sciences, 2022)
Diabetes mellitus is a group of metabolic conditions categorized by anomalous secretion of insulin and metabolic activity. It goes without saying that the general health and oral health are related with each other. Aim: The aim of the analysis was to evaluate oral complications in patients with and without diabetes, as well as to evaluate oral knowledge and practice. Place and Duration: In the dental department of Ayub Medical College, Abbottabad and Islamic International Dental College, Islamabad for six-months duration from July 2021 to December 2021. Methods: The study was conducted on diabetic and nondiabetic women and men who came to the dental hospital for dental and oral treatment. The researcher asked questions orally in Urdu and complete the questionnaire form which comprised the dental, oral hygiene and diabetic related questions. 180 total people (100 diabetic patients and 80 non-diabetic patients) answered the questionnaire. The patients sample mean age was 48.20 (SD 7.10), diabetic patients mean age was 47.2 (SD 7.05), and non-diabetic patients mean age was 47.80 (SD 7.10). The patients age range varies from 30 to 70 years of age. 41.7% of the patients were women and 58.3% were men. Conclusions: The survey showed that the awareness, practice and oral health of patients with diabetes in our community are poor. Information on oral health was lacking in both the diabetic and nondiabetic groups.